Effect of internal erosion on the hydraulic behavior of gap-graded coarse-fine mixtures: Experimental and mathematical investigations - Marziyeh Salajegheh; Mahmoud Yazdani; Vahid Pachideh (Transportation Engineering)
Internal erosion is a phenomenon in which fine particles are removed by seepage through pore channels between coarse particles in internally unstable soil. It can lead to widespread pavement collapse or sinkholes, undesirable incidents in tunnel engineering and dike foundations, and clogging of oil wells. The erodibility of soil is influenced by critical factors such as the plasticity index (PI) and fines content (FC). However, the combined effects of these factors on internal erosion remains uncertain. For this reason, in this research a triaxial-erosion apparatus was developed to perform an experimental and mathematical investigation of erosion of sand-fines mixtures. Three different clay-sized particle types (rock powder, kaolinite or bentonite) each with three fines contents 20 %, 25 % and 30 % were used. The results indicated that while the output velocity initially rose rapidly with an increasing hydraulic gradient during the early stages of erosion, hydraulic conductivity eventually decreased due to the clogging of particles in specific areas and the blockage of flow paths. The non-Darcy flow behavior resulting from internal erosion positively impacted seepage control in tested soils. Increasing the PI and fines content enhanced the stability of the sample, as PI had a significant impact on the flow in soils with a higher FC. It was seen that rapid erosion was experienced by rock powder mixtures before stabilization, gradual erosion occurred in bentonite due to high cohesion, and uniform erosion was exhibited by kaolinite without significant flocculation. Following erosion, the granulation results of various soil layers clarified three interconnected internal erosion processes: reattachment, rearrangement, and transport. In this study, an equation is derived that describes the variation in the eroded mass with respect to the hydraulic gradient, time, PI and FC.